Generalized mean function - Hussain Battor, Ali; Ali Shubber, Hadeel (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In 1969 S.K.Skaff introduced the generalized mean function In this work we present the theory of an integral mean for generalized GN*-function .We will show under what conditions the mean function is a GN*-function and satisfies a condition. Moreover, we examine how the minimizing points in the definition of the mean function affect a basic property of the ordinary integral mean.